A system‐size independent validation of CFD‐DEM for noncohesive particles. Issue 12 (5th October 2015) - LaMarche, Casey Q.; Liu, Peiyuan; Kellogg, Kevin M.; Weimer, Alan W.; Hrenya, Christine M.
Significance: For the first time, CFD‐DEM simulations of small‐scale fluidized beds are quantitatively validated against large‐scale experiments. Such validation is possible via the identification of a measurement independent of system size, namely defluidization. CFD‐DEM inputs (particle properties and operating conditions) are measured directly. Sphericity is found to be critical, even for highly spherical particles. This size‐independent method of validation is valuable since it allows for validation of CFD‐DEM models without restrictions on system sizes or particle sizes. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4051–4058, 2015